2012
DOI: 10.1140/epjc/s10052-012-1894-4
|View full text |Cite
|
Sign up to set email alerts
|

Localizability of tachyonic particles and neutrinoless double beta decay

Abstract: The quantum field theory of superluminal (tachyonic) particles is plagued with a number of problems, which include the Lorentz non-invariance of the vacuum state, the ambiguous separation of the field operator into creation and annihilation operators under Lorentz transformations, and the necessity of a complex reinterpretation principle for quantum processes. Another unsolved question concerns the treatment of subluminal components of a tachyonic wave packets in the field-theoretical formalism, and the calcul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
109
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(116 citation statements)
references
References 44 publications
7
109
0
Order By: Relevance
“…[22] and recently subject to a few more investigations reported in Refs. [52][53][54][55]. It is based on the Lagrangian…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22] and recently subject to a few more investigations reported in Refs. [52][53][54][55]. It is based on the Lagrangian…”
Section: Discussionmentioning
confidence: 99%
“…Quite recently [52,53,55], it has been shown that the solutions of Eq. (A2) have an convenient structure in helicity basis [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrarelativistic transform leads to a form which asymptotically is equal to the Weyl Hamiltonian (helicity basis) of a massless particle, as it should be (in the ultrarelativistic limit). Here, we shall make the point that, unlike the original Foldy-Wouthuysen transform, which can only be applied to tardyons, the ultrarelativistic decoupling can also be used for Lorentz-invariant tachyons [12,19,20], whose velocity remains superluminal upon Lorentz transformation [13][14][15][16][17].…”
Section: B Free Tachyonic Transformationmentioning
confidence: 99%
“…The accepted generalized Dirac Hamiltonian for a free tachyonic Dirac particle is given as [12,19,20] …”
Section: B Free Tachyonic Transformationmentioning
confidence: 99%